The influence of flexibility of work to loyalty and employee satisfaction mediated by work life balance to employees with millennial generation background in Indonesia startup companies - Capnary, Muhammad Calvin; Rachmawati, Riani; Agung, Iskandar (Business: Theory and Practice, 2018)
Human resource is the one of the most important elements in the company. Therefore, the company must have related strategies to retain these workers. One of them is by increasing employee loyalty and satisfaction through flexibility of work and work life balance. The strategy chosen is based on the unique characteristics of the majority of workers who entered the millennial generation. Some companies are already implementing these strategies, including startup companies. This study aims to investigate the influence of the flexibility of working on loyalty and employee satisfaction with work life balance. This research was conducted using convenience and snowball sampling technique to the 121 respondents with a millennial generation background which is worked in startup companies in Indonesia. Data obtained from respondents were processed and analyzed using structural equation modeling. The results of this study indicate that flexibility of work has significant and positive influence to loyalty and employee satisfaction. However, flexibility of work has positive and significant impact on loyalty and employee satisfaction. This research prove that work life balance have partial mediating influence in relationship between flexibility of work and loyalty. In the other hands, work life balance have no mediating a relationship between flexibility of work and the satisfaction of employee with millennial background that is worked in startup companies.